Intraday information from S&P 500 index futures options - LIM, Kian Guan (Institutional Knowledge at Singapore Management University, 2019)
In this paper we employ intraday transaction prices of liquid E-mini S&P 500 index futuresoptions to form 10-minutes ahead risk-neutral skewness forecasts and show profitable optionstrading strategy net of transaction costs. We do not find profitable trading based on 10-minutesahead risk-neutral volatility and only very marginal cases of profitable trading using kurtosisforecasts. The skewness profitability anomaly may be an indication of informational marketinefficiency in intraday S&P 500 futures options markets, which is contrary to findings usinglonger-span daily and weekly moments. Our results lend credence to the persistence of intradaytrading activities in the markets.